Análise dos efeitos nos dividendos das empresas de capital aberto inscritas na BM&FBovespa, do segmento de siderurgia e metalurgia, após a promulgação da Lei nº 11.638/07 - Correia, Paula Valéria Chaves Pereira (2012)
The purpose of this research is to analyze the effects of changes in accounting legislation introduced by Law 11.638/07 in dividends paid to shareholders, through a study on equity and net income. To develop this work companies in the Steel & Metals segments were taken as base with shares listed on the BM & FBovespa. We analyzed 13 companies that make up the segment, in the period from 2004 to 2007, drawing a comparison with the period from 2008 to 2011, following the entry into force of new accounting standards introduced by Law 11.638/07. The methodology applied was quantitative through the analysis of financial statements of the companies, by statistical methods of testing "distribution Z" often used to measure hypotheses between two samples to determine their acceptance or rejection. At the requirement and application of new standards, this has led to many questions in the companies in view of the high degree of complexity of the measures implemented. However, the conclusion of the survey, conducted through analysis of financial statements and statistical methods, was that the changes in accounting standards did not affect net income and consequently the dividends paid to shareholders